The impact of prudent financial policies on the urban–rural household health expenditure disparity: evidence from China - Zou, Wenxin; Dai, Zihui; Li, Xijie (Frontiers in Public Health, 2025)
IntroductionWith the rapid development of China’s financial markets, the impact of proactive financial policies on household health investment has drawn significant attention, yet little is known about the effects of prudent financial policies on household health expenditures. We examine the effects of a prudent financial policy called the New Asset Management Regulation (NAMR). The policy aims to reduce systemic financial risks by breaking rigid payments and regulating shadow banking. The introduction of the policy expands research in this field.MethodsThis study employs the intensity difference-in-differences (intensity DID) approach, utilizing data from the China Family Panel Studies (2012–2020), to assess the effects of the NAMR. We further construct interaction terms between household existing capital (both tangible and intangible) and the key explanatory variables to test the heterogeneity of the baseline results.ResultsThe results show that the regulation significantly affects rural households’ medical expenditures (with a 20.5% decrease in guaranteed investment and a 1.3% increase in out-of-pocket payments), but has no significant impact on urban households. Heterogeneity analysis shows urban households’ health investment reduces health spending by 0.067%, moderated negatively by tangible assets (property) and positively by intangible assets (business experience, social ties). For households with business experience, a 10% treatment intensity increase raises health spending by 5.4%. A simultaneous 10% treatment intensity and 1-unit transport spending increase boosts health expenditures by 5.8%, revealing how asset types shape urban–rural health spending differences. Furthermore, post-implementation, urban households’ education expenditures significantly increased, while migrant households experienced a rise in guaranteed investment and a decline in out-of-pocket payments, though not statistically significant.DiscussionThis study highlights the multifaceted impact of prudent financial policies on household health expenditures across urban and rural areas, underscoring the need for policy formulation to address the distinct needs of urban, rural, and migrant populations, thereby laying a more solid institutional foundation for universal health coverage.